Beneficial Effects of Spirulina Aqueous Extract on Vasodilator Function of Arteries from Hypertensive Rats - Diva M. Villalpando; Carlos M. Verdasco-Martín; Ignacio Plaza; Juan Gómez-Rivas; Fermín R de Bethencourt; Morris Villarroel; José L. García; Cristina Otero; Mercedes Ferrer (International Journal of Vascular Medicine)
Hypertension is a multifactorial disorder considered one of the major causes of premature death worldwide. This pathology is associated with vascular functional/structural alterations in which nitric oxide (NO) and oxygen reactive species participate. On the other hand, the use of microalgae extracts in the treatment of cardiovascular diseases is increasing. Based on the antioxidant and antihypertensive properties of Spirulina, this study aims to investigate the effect of an aqueous extract of Spirulina on the vasodilator function of the aorta from spontaneously hypertensive rats (SHR), analyzing the functional role of NO. For this, aortic segments from male SHR were divided into two groups, one control and the other exposed to an Spirulina aqueous extract (0.1% w/v, for 3 hours), to analyze (i) the production of NO, superoxide anion, and hydrogen peroxide; (ii) the vasodilator response induced by acetylcholine (ACh), by the NO donor and sodium nitroprusside (SNP), and by the KATP channel opener and pinacidil; and (iii) the expression of the p-Akt, p-eNOS, and HO-1 proteins. The results showed that the aqueous Spirulina extract (i) increased the production of NO, did not significantly modify that of superoxide, while decreased that of hydrogen peroxide; (ii) increased the vasodilatory responses induced by ACh, NPS, and pinacidil; and (iii) increased the expression of p-Akt and HO-1. These results suggest that incubation with the aqueous Spirulina extract improves the vascular function of arteries from SHR by increasing the release/bioavailability/function of NO. Increased KATP channel activation and expression of pAkt and HO-1 appear to be participating in these actions.